Effects of fatigue on physiological, physical fitness, and stroke performance related parameters in healthy tennis players: a systematic review and meta-analysis - Lambrich, Johanna; Muehlbauer, Thomas (Frontiers in Sports and Active Living, 2025)
Fatigue is a multifactorial phenomenon involving central and peripheral mechanisms that could negatively affect performance-related measures in tennis players. The aim of this systematic review and meta-analysis was to quantify the effects of fatigue on physiological (e.g., blood lactate, heart rate), physical fitness (e.g., explosive muscle strength, speed), and stroke performance (e.g., stroke velocity or accuracy) related parameters in healthy tennis players and to provide insight into training and recovery strategies. A systematic literature search of PubMed, Web of Science, and SportDiscus identified studies that examined effects of fatigue in tennis. Inclusion criteria required that studies were conducted with healthy participants, applied fatigue-inducing interventions, and used pre-/post-test designs measuring physiological, physical, or stroke performance related parameters. Effect sizes were calculated using weighted standardized mean differences (SMD) to assess the impact of fatigue. The search identified a total of N = 642 records. Eighteen trials (318 tennis players) were included. Fatigue evoked large to moderate negative effect on physiological (SMDw = −4.19), physical fitness (SMDw = −0.74), and stroke performance (SMDw = −0.60) related parameters. The larger negative effects of fatigue on physiological and physical parameters compared to stroke performance-related outcomes indicate the importance of targeted recovery strategies (e.g., hydration, nutrition or cold baths). For stroke performance, non-fatigued states are recommended for learning new skills, while practice under fatigued conditions may help to maintain biomechanical efficiency during prolonged games.